The Influence of Leadership, Organizational Culture and Career Development on the Work Ethic of Police Members at the North Jakarta Metro Police - Edi Purnawan (Privietlab, 2022)
This study examined whether leadership, organizational culture, and career development influence police work ethics in a public-service security institution. The empirical design was a quantitative correlational survey using simple random sampling, with 76 respondents drawn from an accessible population of 312 brigadier-level personnel in operational units. Leadership, organizational culture, and career development were treated as independent variables, and work ethic was the dependent variable. The findings show that all three predictors significantly affect work ethic, both individually and jointly. Leadership explained 46.4% of the variance in work ethic, organizational culture 47.4%, and career development 44.2%. Simultaneously, the three variables produced a strong positive relationship (R = .750) and explained 56.2% of the variance in the dependent variable. Among the three predictors, organizational culture made the largest individual contribution. These results indicate that police work ethics are shaped not only by formal rules but also by leadership quality, shared organizational norms, and the credibility of career opportunities. The updated discussion situates the original findings within 2021 organizational and human resource scholarship, which highlights the importance of leadership, culture, and development systems for employee behavior and performance.